2014
DOI: 10.1590/rou.2014.048
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera as vehicle to mineral trioxide aggregate: study in bone repair

Abstract: AIM: Mineral trioxide aggregate (MTA) was associated to Aloe vera to verify the coadjutant action of that medicinal plant in the bone neoformation process in tibia of rats.MATERIAL AND METHOD: 36 male rats (Rattus norvegicus) were used, divided into two groups of 18 rats each. Two circumferential bone defects with approximately 5 mm in diameter were made on the right tibia of each animal: the upper defect was filled with blood coagulates in both groups to serve as experimental control and the lower defect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
2
0
4
Order By: Relevance
“…The Aloe vera was used in the study as an anti-inflammatory factor to aid in bone repair. 11 , 23 , 24 Statistically significant (p<0.05) inflammatory infiltration results were found in our research, where the groups treated with the herbal medicine showed better results. The reduction of inflammation may be explained by the anti-inflammatory properties of Aloe vera , due to the immunomodulatory effect of acetylated polysaccharides mannose, acemannan and veracilglucanos B and C, which regulate the expression of inflammatory mediators such as interleukins 6 and 8.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The Aloe vera was used in the study as an anti-inflammatory factor to aid in bone repair. 11 , 23 , 24 Statistically significant (p<0.05) inflammatory infiltration results were found in our research, where the groups treated with the herbal medicine showed better results. The reduction of inflammation may be explained by the anti-inflammatory properties of Aloe vera , due to the immunomodulatory effect of acetylated polysaccharides mannose, acemannan and veracilglucanos B and C, which regulate the expression of inflammatory mediators such as interleukins 6 and 8.…”
Section: Discussionsupporting
confidence: 61%
“…23 Similar results were observed in the treatment of bone defects using Mineral Trioxide Aggregate and Aloe vera , with significant reduction of the inflammatory cascade’s effects. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Além disso, destaca-se seu potencial cicatrizador e anti-inflamatório, que pode ser um coadjuvante no tratamento de patologias endodônticas 14,22 quando aliado a outras medicações intracanais. Sua utilização como veículo para o Mineral Trióxido Agregado (MTA), por exemplo, demonstrou redução significativa dos efeitos da cascata inflamatória em experimentos in vivo 12 .…”
Section: Resultadounclassified
“…No intuito de melhorar a pasta utilizada como medicação intracanal, o Aloe vera (AV), membro da família das Liliáceas, tem sido avaliado como veículo para o hidróxido de cálcio 4 . Popularmente conhecido como babosa, esse fitoterápico se destaca pela sua capacidade imunorreguladora, antimicrobiana, cicatrizante e pela biocompatibilidade celular [10][11][12][13][14][15][16][17] Dessa forma -e posto que a atividade de reparo tecidual e a ação antimicrobiana são fatores importantes no sucesso do tratamento endodôntico -, o objetivo deste estudo foi avaliar a dissociação iônica do hidróxido de cálcio, tendo Aloe vera como veículo.…”
unclassified
“…O Aloe vera (Aloe barbadensis Miller), membro da família das Liliaceae, tem sido avaliado nos mais diversos campos da odontologia, dos quais destacam-se sua atuação na cicatrização de lesões orais (Ali;Wahbi, 2017). Popularmente conhecida como babosa, a espécie Aloe vera contém diversas substâncias biologicamente ativas, capazes de proporciornar importantes propriedades anti-inflamatórias, antibacterianas, hipoglicêmicas, imunomoduladoras, cicatrizantes e regenerativas (Abbaszadegan et al, 2016;Jittapiromsak et al, 2010;Fani;Kohanteb, 2012;Fé et al, 2014).…”
Section: Introductionunclassified